Factor V Leiden, Antiphospholipid Antibodies and Thrombosis in Systemic Lupus Erythematosus - Fijnheer, R; Horbach, D A; Donders, R C J M; Vilé, H; Oort, E v; Nieuwenhuis, H K; Gmelig-Meijling, F H J; de Groot, Ph G; Derksen, R H W M (Thrombosis and Haemostasis, 1996)
Thromboembolic complications are frequently observed in patients with systemic lupus erythematosus (SLE). Significant associations have been reported between these complications and the presence of antiphospholipid antibodies, notably the lupus anticoagulant and anti-cardiolipin antibodies. Factor V Leiden is a genetic disorder associated with an increased risk of venous thrombosis. We studied these factors in 173 patients with SLE in relation to both arterial and venous thrombosis. The frequency of factor V Leiden in SLE patients is comparable to that in the Dutch population (5%) and a risk factor for venous thrombosis (odds ratio 4.9; Cl 1.2-19.6), but not for arterial thrombosis. The lupus anticoagulant is a risk factor for both arterial thrombosis (odds ratio 7.1; Cl 2.9-17.4) and venous thrombosis (odds ratio 6.4; Cl 2.7-15.4). From multivariate analysis, both the lupus anticoagulant and factor V Leiden appeared independent risk factors for venous thrombosis.